Achievement of Students in Biology in Relation to Demographic Variables - Yadav, Manoj Kumar; Singh, Vinod Kumar (SCHOOL SCIENCE, 2018)
The present study is aimed to investigate the achievements in Biology of Class XI students in relation to the demographic variables, i.e. gender, locale, age and caste. A sample of 300 students was randomly selected from six schools of Varanasi city in Uttar Pradesh. For obtaining the data, biology achievement was recorded by self-made achievement test. Statistical analysis was made by calculating mean, standard deviation, t-test and anova. The findings of the study suggest that there is a significant difference in the biology achievement of various caste categories of the students but other demographic variables such as gender, locale and age do not bring in any significant difference in biology achievement of Class XI students at formal operational stage.